2014
DOI: 10.1186/s12866-014-0220-8
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnical paving of recombinant enterocin A as the candidate of anti-Listeriaagent

Abstract: BackgroundEnterocin A is a classic IIa bacteriocin isolated firstly from Enterococcus faecium CTC492 with selective antimicrobial activity against Listeria strains. However, the application of enterocin A as an anti-Listeria agent has been limited due to its very low native yield. The present work describes high production of enterocin A through codon optimization strategy and its character study.ResultsThe gene sequence of enterocin A was optimized based on preferential codon usage in Pichia pastoris to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…To determine the bacteriocin thermostability, solutions containing the bacteriocin were firstly treated at 60°C, 80°C, and 100°C for 15 and 30 min, and 121°C for 15 min. Then, the samples’ antimicrobial activity was measured through the microtiter plate assay (Hu et al., 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the bacteriocin thermostability, solutions containing the bacteriocin were firstly treated at 60°C, 80°C, and 100°C for 15 and 30 min, and 121°C for 15 min. Then, the samples’ antimicrobial activity was measured through the microtiter plate assay (Hu et al., 2014).…”
Section: Methodsmentioning
confidence: 99%
“…for 15 and 30 min, and 121°C for 15 min. Then, the samples' antimicrobial activity was measured through the microtiter plate assay (Hu et al, 2014).…”
Section: Effects Of Ph Temperature and Storage Time On The Bactermentioning
confidence: 99%
“…Mundticin KS showed an antimicrobial activity of 6,400 to 12,800 AU/mL-1 when produced in a fermenter (Kawamoto et al, 2002). Xiaoyuan et al (2014) showed the highest antilisteria activity reaching 51,200 AU/mL-1 from enterocin A after 24 h of induction in a 5 L fermenter. The ACs-J5 were stable within a wide range of pH and heat treatment and sensitive to all proteolytic enzymes tested, suggesting their proteinaceous nature.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial peptides (AMPs) are natural products that show promise in antibacterial applications for both the health care and food industries (Drider et al, ; Grosu‐Tudor et al, ; Hu et al, ; Kjos et al, ; Snyder and Worobo, ; Zhao et al, ). AMPs are typically cationic, amphiphilic peptides that serve as defense proteins for the producing organism (Drider et al, ; Fimland et al, ; Hwang and Vogel, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriocins are a specific group of AMPs that are produced by bacteria and, when created by LAB, are typically heat‐stable (Drider et al, ; Tagg et al, ). Bacteriocins have been studied for their potential in antibacterial applications both in the health care and food industries (Drider et al, ; Grosu‐Tudor et al, ; Hu et al, ; Kjos et al, ; Snyder and Worobo, ; Zhao et al, ). Enterocin A (entA) is a class 2a bacteriocin isolated from E. faecium CTC492 and shows inhibition of E. faecalis, Pediococcus, Listeria , and some strains of E. faecium (Aymerich et al, ).…”
Section: Introductionmentioning
confidence: 99%